Health-Related Quality of Life Is Low in Secondary School Children in Fiji. (4th December 2012) - Petersen, Solveig; Mavoa, Helen; Swinburn, Boyd; Waqa, Gade; Goundar, Ramneek; Moodie, Marjory
Abstract : The health and wellbeing of children in lower-income countries is the focus of much international effort, yet there has been very little direct measurement of this. Objective. The current objective was to study the health-related quality of life (HRQoL) in a general population of secondary school children in Fiji, a low middle-income country in the Pacific. Methods . Self-reported HRQoL was measured by the Pediatric Quality of Life Inventory 4.0 in 8947 school children (aged 12–18 years) from 18 secondary schools on Viti Levu, the main island of Fiji. HRQoL in Fiji was compared to that of school-aged children in 13 high- and upper middle-income countries. Results . The school children in Fiji had lower HRQoL than the children in the 13 comparison countries, with consistently lower physical, emotional, social, and school functioning and wellbeing. HRQoL was particularly low amongst girls and Indigenous Fijians. Conclusions . These findings raise concerns about the general functioning and wellbeing of school children in Fiji. The consistently low HRQoL across all core domains suggests pervasive underlying determinants. Investigation of the potential determinants in Fiji and validation of the current results in Fiji and other lower-income countries are important avenues for future research.